Outcomes of Sepsis and Septic Shock in Cancer Patients: Focus on Lactate - López, René; Pérez-Araos, Rodrigo; Baus, Fernanda; Moscoso, Camila; Salazar, Álvaro; Graf, Jerónimo; Montes, José Miguel; Samtani, Suraj (Frontiers in Medicine, 2021)
The number of oncological patients (OP) admitted in intensive care unit (ICU) for sepsis/septic shock has dramatically increased in the recent years. Additionally, septic shock definition has been modified adding hyperlactatemia as a severity biomarker for mortality, however, remains poorly reported in septic OP. We performed a retrospective analysis from a prospective data base of sepsis/septic shock patients admitted in our ICU between September 2017 and September 2019 and followed until day 90. We identified 251 patients and 31.9% had active oncological comorbidity, mainly solid tumor (81.3%). Septic shock criteria were met for 112 (44.6%). Hyperlactatemia was observed in 136 (54.2%) patients and this was associated with a lower survival. Overall 90-day mortality was 15.1%. In OP versus non-OP, hyperlactatemia was more frequent (65% vs 49.1%, p=0.013) and associated with lower survival (65.4% vs 85.7%, p=0.046). In OP, poor performance status was also associated with lower survival (HR 7.029 [1.998-24.731], p=0.002) In an adjusted analysis, cancer was associated with lower 90-day survival (HR 2.690 [1.402-5.160], p=0.003). In conclusion, septic OP remains as a high mortality risk group in whom lactate levels and performance status could help to better risk stratification.